2018
DOI: 10.1039/c8lc00386f
|View full text |Cite
|
Sign up to set email alerts
|

Detecting miRNA biomarkers from extracellular vesicles for cardiovascular disease with a microfluidic system

Abstract: According to World Health Organization reports, cardiovascular diseases (CVDs) are amongst the major causes of death globally and are responsible for over 18 million deaths every year. Traditional detection methods for CVDs include cardiac computerized tomography scans, electrocardiography, and myocardial perfusion imaging scans. Although diagnosis of CVDs through such bio-imaging techniques is common, these methods are relatively costly and cannot detect CVDs in their earliest stages. In contrast, the levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 46 publications
0
43
0
Order By: Relevance
“…In this study, 2MBB was conducted with minimal special equipment required, and an overnight mixing of magnetic beads with the sample is required to attain the desired EV yield. It can be readily integrated with microfluidic systems to provide the precise and automatic control of the process and to shorten the mixing time [21,42,43]. The throughput can be further improved by utilizing field-effect transistor (FET) sensors to detect miRNAs directly without PCR amplification [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 2MBB was conducted with minimal special equipment required, and an overnight mixing of magnetic beads with the sample is required to attain the desired EV yield. It can be readily integrated with microfluidic systems to provide the precise and automatic control of the process and to shorten the mixing time [21,42,43]. The throughput can be further improved by utilizing field-effect transistor (FET) sensors to detect miRNAs directly without PCR amplification [44].…”
Section: Discussionmentioning
confidence: 99%
“…In order to increase the yield and purity of enriched EVs, we built on prior reported immune-affinity based techniques [14,20,21] and developed a two-step magnetic bead-based (2MBB) approach to recover EVs and EV-associated miRNAs. Micro-magnetic beads coated with capture molecules against EV-specific surface markers, such as CD63, could improve the enrichment process due to the high surface-to-volume ratio of beads.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al demonstrated the usefulness of microencapsulation in combination with a particle counter for digital analysis to detect miRNAs directly from plasma in less than 3 hours and down to 10 single copies of miRNA. The device was able to detect miRNA with a limit of detection of about 50 copies per mL of plasma and was thus able to distinguish healthy donor samples from those originating from patients with metastatic colon cancer based on detection of Let-7a levels 60 magnetically attracted to the extraction solvent (blue) held by a magnetic rod (grey) 59 , c) Magnetic beads coated in anti-CD-63 antibodies for exosome isolation 61,62 , d) Surface acoustic waves for extracellular vesicle lysis 63 .…”
Section: On-chip Mirna Extraction and Detectionmentioning
confidence: 99%
“…Affinity‐based isolation of exosomes on chips usually relies on capture probes (typically antibodies or aptamers) to identify generic membrane markers (e.g., CD9 and CD63) or specific exosome biomarkers, such as epithelial cell adhesion molecule (EpCAM), EGFR, melanoma cell adhesion molecule, and melanoma‐associated chondroitin sulfate proteoglycan. [ 101–106 ] Compared to size‐based methods, which can only retrieve total exosomes from bio‐fluids, immunocapture on chip provides an opportunity for separating either total exosomes or sub‐type exosomes. Generally, there are two main types of immunocapture‐on‐a‐chip strategies.…”
Section: Microfluidics‐based Exosome Isolationmentioning
confidence: 99%